Influence Of Scaler Tip Design On Intensity Of Pain And Discomfort During Scaling - Mohamad Hanis Mat Nazri; Mohd Fakhrul Ridwan Mohd Azmi; Nor Adinar Baharuddin; Roslan Saub; Nur Ayman Abdul Hayei; Rathna Devi Vaithilingam (Universiti Malaya, 2024)
Ann Dent UM. 2018, 25(2): 36-42